Childhood trauma, substance use and mental health: Exploring differences across two Tunisian jails - Aya Ajmi Blout; Imen Mlouki; Emna Hariz; Mariem Meherzi; Abla Chefai; Mariem Triki; Marwa Boussaid; Helen Snooks; Abir Aouissaoui; Sana El Mhamdi (PLoS ONE, 2026)
Introduction The increasing rate of incarceration represents a significant public health issue worldwide. However, focusing on mental health issues and exploring gender differences among this vulnerable population is lacking in the literature. We aimed to assess differences in childhood trauma, substance use, and mental health among two Tunisian jails. Materials and methods Two cross-sectional studies were conducted in two Tunisian prisons with different gender compositions, one involving male prisoners in April 2023 and the other involving female prisoners in July 2024. We used Arabic-validated versions of the Adverse Childhood Experiences-International Questionnaire, the Hospital Anxiety and Depression Scale, and the Rosenberg Self-Esteem Scale. Substance use and suicidal thoughts were assessed through a yes or no question. The questionnaire was anonymous and participation was voluntary. Results A total of 568 prisoners answered the questionnaire. The majority were males (71%) with a median age of 31 years [2640]. We found that participants from female prison reported higher rates of childhood sexual abuse (25.6% vs 7.8%, p < 0.001). Physical abuse was more common among the male prison population (74.6% vs 58.8%, p < 0.001). Community and collective childhood violence were significantly more prevalent among participants from the male prison (94.8% vs 74.5%, p < 0.001 and 57.3% vs 43.6%, p = 0.003, respectively). Substance use was more prevalent among participants in the male prison across all substance types assessed. The female prison population reported more severe anxiety symptoms (69.1% vs 23.6%, p < 0.001) and depressive symptoms (96.4% vs 80.1%, p < 0.001). About 46% of participants in the female prison reported suicidal thoughts during incarceration, compared with 35.1% in the male prison (p = 0.014). The male prison population was more likely to have lower self-esteem (87.4% vs 69.1%, p < 0.001). Conclusion Implementing rehabilitation programs for prisoners is essential to reduce incarceration rates and mitigate these alarming negative outcomes.